Inflammatory Bowel Disease and Skin Cancer: An Assessment of Patient Risk Factors, Knowledge, and Skin Practices. (29th February 2016) - Kimmel, Jessica N.; Taft, Tiffany H.; Keefer, Laurie
Abstract : Objective . Patients with inflammatory bowel disease (IBD) are at increased risk from skin cancer. Aims include assessing IBD patients' risk factors and knowledge of skin cancer and current skin protection practices to identify gaps in patient education regarding skin cancer prevention in IBD. Methods . IBD patients≥ 18 years were recruited to complete an online survey. Results . 164 patients (mean age 43.5 years, 63% female) with IBD (67% Crohn's disease, 31% ulcerative colitis, and 2% indeterminate colitis) were included. 12% (n = 19 ) of patients had a personal history and 34% (n = 55 ) had a family history of skin cancer. Females scored better on skin protection (16.94/32 versus 14.53/32, P ≤ 0.03 ) and awareness (35.16/40 versus 32.98/40, P ≤ 0.03 ). Patients over 40 years old scored better on prevention (17.45/28 versus 15.35/28, P = 0.03 ). Patients with skin cancer scored better on prevention (20.56/28 versus 15.75/28, P ≤ 0.001 ) and skin protection (21.47/32 versus 15.33/32, P ≤ 0.001 ). 61% of patients recognized the link between skin cancer and IBD. Conclusions . The majority of IBD patients are aware of the link between skin cancer and IBD; however, skin protection practices are suboptimal. This emphasizes the role of healthcare professionals in providing further education for skin cancer prevention in the IBD population.